2014
DOI: 10.1111/ina.12097
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of stratum-ventilated thermal environment and thermal sensation

Abstract: Three human test series were conducted to evaluate the uniformity of the thermal environments in a stratum-ventilated chamber with dimensions of 8.8 m (L) × 5.1 m (W) × 2.4 m (H). In all, nineteen conditions were generated by adjusting the room temperature, supply airflow rate, and supply terminal type. An air diffuser performance index (ADPI) of at least 80% was achieved for most cases. This result shows that the air velocity and temperature in the occupied zone are reasonably uniform. Subjective assessments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 13 publications
1
43
0
Order By: Relevance
“…For the supply airflow rates of 7 ACH, 10 ACH and 15 ACH, the average thermal sensation was 0.07, 0.13, and −0.08, respectively. This indicated that the subjects felt neutral at the room temperature of 27 °C, which is in agreement with the findings of our previous studies (Cheng et al., ; Fong et al., ).…”
Section: Results and Discussion: Subjective Thermal Comfort Surveysupporting
confidence: 93%
“…For the supply airflow rates of 7 ACH, 10 ACH and 15 ACH, the average thermal sensation was 0.07, 0.13, and −0.08, respectively. This indicated that the subjects felt neutral at the room temperature of 27 °C, which is in agreement with the findings of our previous studies (Cheng et al., ; Fong et al., ).…”
Section: Results and Discussion: Subjective Thermal Comfort Surveysupporting
confidence: 93%
“…Subjective surveys of stratum ventilation also confirmed the deficiency of the conventional control method [27,28]. Even with proper control, the percentage of occupants feeling thermal comfort was generally from 80% to 90%, leaving the remaining occupants suffering from thermal discomfort [27,28].…”
Section: Introductionmentioning
confidence: 81%
“…The widely used thermal comfort model, PMV-PPD, echoes the deficiency of the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 conventional control method that even under the optimal condition, at least 5% occupants would feel dissatisfied with the thermal environment [26]. Subjective surveys of stratum ventilation also confirmed the deficiency of the conventional control method [27,28]. Even with proper control, the percentage of occupants feeling thermal comfort was generally from 80% to 90%, leaving the remaining occupants suffering from thermal discomfort [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a neutral OTS ensured satisfactory OTC. It may be attributed to the thermal uniformity in the occupied zone under stratum ventilation [30]. Fig.…”
Section: Thermal Sensation and Comfortmentioning
confidence: 95%
“…Perforation diffusers and double deflection grilles were used as the supply and return terminals respectively because they had exhibited good performance in a previous study [30]. Three room temperature settings (24 C, 27 C and 29 C) were applied in this series while the supply airflow rate was kept constant at 10 ACH.…”
Section: Experimental Designmentioning
confidence: 99%